Seasonal variation of dinitrogen fixation and assimilation of nitrate in tropical forage grasses - Souto, Sebastião Manhães; Dobereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was carried out to study the seasonal patterns of N2-fixation, assimilation of nitrate and population of N2-fixing bacteria on roots of tropical forage grasses under frequent nitrate applications. The grasses used were: Hyparrhenia rufa (Jaraguá), Digitaria decumbens (cvs. Pangola A-21 and Transvala) and Pennisetum purpureum (cvs. Napier and Cameron). Rainfall and nitrogenase activity were positively correlated (r = 0,76**), especially with the cultivar Cameron, the genotype which showed in general highest nitrogenase activities. There was no difference in. nitrogenase activity among cultivares during the dry season. The effects of fertilization with nitrogen on nitrate reductase activities lasted up to four weeks after each fertilizer application. All genotypes contained less than 10% of the bacteria inside the root, which however in three cultivars, Cameron (r = 0,66**), Pangola (r = 0,45*) and Transvala (r = 0,41*), were significantly correlated with nitrogenase activity of she roots. The larger external population showed no correlation with the nitrogenase activity